Tomato fruit quality is more strongly affected by scion type and planting season than by rootstock type - Gong, Tian; Brecht, Jeffrey K.; Hutton, Samuel F.; Koch, Karen E.; Zhao, Xin (Frontiers in Plant Science, 2022)
Previous studies of tomato rootstock effects on fruit quality have yielded mixed results, and few attempts have been made to systematically examine the association between rootstock characteristics and tomato fruit quality. In this study, grape tomato (‘BHN 1022’) and beefsteak tomato (‘Skyway’) were grafted onto four rootstocks [‘Estamino’ (vigorous and “generative”), ‘DR0141TX’ (vigorous and “vegetative”), ‘RST-04-106-T’ (uncharacterized), and ‘SHIELD RZ F1 (61–802)’ (mid-vigor, uncharacterized)] and compared to non-grafted scion controls for two growing seasons (Spring and Fall in Florida) in organically managed high tunnels. In both seasons and for both scions, the two vigorous rootstocks, regardless of their designation as “vegetative” (‘DR0141TX’) or “generative” (‘Estamino’), exhibited negative impacts on dry matter content, soluble solids content (SSC), SSC/titratable acidity (TA), lycopene, and ascorbic acid contents. Similar effects on fruit dry matter content and SSC were also observed with the ‘RST-04-106-T’ rootstock, although little to no change was seen with grafting onto ‘SHIELD RZ F1 (61–802)’. Further studies are needed to elucidate the impact of rootstock vigor on tomato volatile profiles and consumer sensory acceptability in order to better determine whether any of the documented effects are of practical importance. On the other hand, the evident effects of scion cultivar and planting season on fruit quality were observed in most of the measurements. The scion by rootstock interaction affected fruit length, firmness, pH, and total phenolic content, while the planting season by rootstock interaction impacted fruit firmness, pH, total antioxidant capacity, and ascorbic acid and lycopene contents. The multivariate separation pattern of planting season, scion, and rootstock treatments as revealed by the canonical discriminant analysis further indicated that the influence of scion cultivar and planting season on tomato fruit quality could be much more pronounced than the rootstock effects. The fruit color (C* and H°), length and width, SSC, pH, total antioxidant capacity, ascorbic acid, and lycopene contents were the main attributes distinguishing different scion-planting season groups.